2020
DOI: 10.1111/1365-2656.13218
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational maternal age effects in nature: Lessons learnt from Asian elephants

Abstract: In Focus Reichert, S., Berger, V., Jackson, J., Chapman, S. N., Htut, W., Mar, K. U., & Lummaa, V. (2019). Maternal age at birth shapes offspring life‐history trajectory across generations in long‐lived Asian elephants. Journal of Animal Ecology, 89, 996–1007. Parental age can have strong effects on offspring life history, but the prevalence and magnitude of such effects in natural populations remain poorly understood. Using a multigenerational dataset of semi‐captive Asian elephants, Reichert et al. (2019) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…[ 106 ] Thus, several studies have also shown that early‐life adversity could trigger a slow pace rather than a fast pace of life in some species or under specific developmental constraints. [ 107 ] In addition, it has also been convincingly demonstrated that there may be an interactive effect of early‐life adversity and environmental conditions encountered during adulthood on the pace of life of organisms. [ 108 ] This suggests that the influence of early‐life adversity on adult telomere dynamics is likely to be mitigated or exacerbated by the severity and the type of early life adversity, by the variability of early‐life conditions, and by the environmental conditions that are encountered during adulthood, as stipulated in the non‐mutually exclusive Resilience hypothesis.…”
Section: Hypotheses On Ultimate Consequence Of Early‐life Adversity O...mentioning
confidence: 99%
“…[ 106 ] Thus, several studies have also shown that early‐life adversity could trigger a slow pace rather than a fast pace of life in some species or under specific developmental constraints. [ 107 ] In addition, it has also been convincingly demonstrated that there may be an interactive effect of early‐life adversity and environmental conditions encountered during adulthood on the pace of life of organisms. [ 108 ] This suggests that the influence of early‐life adversity on adult telomere dynamics is likely to be mitigated or exacerbated by the severity and the type of early life adversity, by the variability of early‐life conditions, and by the environmental conditions that are encountered during adulthood, as stipulated in the non‐mutually exclusive Resilience hypothesis.…”
Section: Hypotheses On Ultimate Consequence Of Early‐life Adversity O...mentioning
confidence: 99%